Inserting Oneself in the Story: Queer Literacy, Comics, and an Admonition to Move - Irene Papoulis; Nicholas P. Marino (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
Inserting Oneself in the Story: Queer Literacy, Comics, and an Admonition to Move
Keywords: Queer Literacies; Comics